THE ABC OF COSMOGRAPHY - Bolotin, Yu. L.; Zazunov, L. G.; Konchatnyi, M. I.; Lemets, O. A. (Одеські астрономічні публікації, 2017)
The basis of this work is the scheme for describing the universe, called the ”cosmography” entirely based on the cosmological principle. Within the framework of such a scheme the parameters of any model that satisfies the cosmological principle (the universe is homogeneous and isotropic on large scale), can be expressed through cosmographic parameters. We demonstrate a number of advantages of the approach used before traditional methods